Requirements Engineering: Foundation for Software Quality: 18th International Working Conference, REFSQ 2012, Essen, Germany, March 19 - 22, 2012; proceedings - Regnell, Björn; Damian, Daniela (Lecture notes in computer science, 2012)
This book constitutes the refereed proceedings of the 18th International Working Conference on Requirements Engineering: Foundation for Software Quality, REFSQ 2012, held in Essen, Germany, in March 2012. The papers are organized in 10 topical sections on contractual requirements, quality requirements, collaboration, complexity and creativity, requirements analysis, templates and heuristics, requirements traceability, tools and quality, services and clouds, self-adaptivity, and industrial case studies.